IMPLIKASI EGOSENTRIS DAN SPIRITUAL REMAJA DALAM MENCAPAI PERKEMBANGAN IDENTITAS DIRI - Sugeng Sejati (JURNAL ILMIAH SYI'AR, 2019)
Adolescence is a period of development that is very important in the dynamics oflife because at this time adolescents have a tendency known as Identity VersusIdentity Confusion which is the main task of adolescents in achieving adevelopment of self-identity. In fact, at this time, many adolescents havedifficulties in recognizing their own identities, what their potential is and wherethey are going, where it becomes a very urgent problem for adolescents. Whilefor the spiritual development of adolescents, it cannot be separated from thedevelopment of the personality as a whole, meaning that one's attitude andspiritual beliefs in his life are none other than his personal role models that growand develop from birth especially since in the womb. The focus of this paper isthe egocentric and spiritual implications of adolescents in achieving thedevelopment of self-identity. This paper is carried out through library researchtechniques. The conclusions of this paper normatively produce an Egocentricand Spiritual Implication of Youth in achieving the development of self-identitywhich makes the next person into a unique and principled person with animportant role in life and value in society.